PENGARUH PENERAPAN CERITA BERGAMBAR TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS II SD - Nisa'ul Ula, Rina Audria; Ni Luh Sakinah Nuraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning basic mathematics literacy in second-grade elementary schools often encounters challenges, especially in understanding word problems related to "turus" (tally marks). This study describes the implementation of picture storybooks and sticker-pasting activities designed to provide visual stimulation that supports students’ visual learning styles. The research applied a qualitative approach with a descriptive-applied method involving 21 second-grade students. Data were collected through observations, teacher’s field notes, and simple literacy tests. The results show that visual stimulation through picture storybooks significantly increases student engagement and enhances understanding of mathematics literacy. Picture storybooks effectively bridge abstract texts into concrete visual contexts, helping students translate word problems into mathematical representations. In conclusion, these visual media are practical and effective tools for supporting basic mathematics learning in elementary schools.